Temporal Variation of Summer Hypoxia off Changjiang Estuary During 1997–2014 and Its Association With ENSO - Ma, Xiao; Liu, Anqi; Zhao, Qiang; Wang, Bin; Tian, Di; Meng, Qicheng; Zeng, Dingyong; Li, Jia; Huang, Daji; Zhou, Feng (Frontiers in Marine Science, 2022)
Temporal variation of summer hypoxia, along a repeated hydrographic section from the Changjiang River mouth to Cheju Island, is investigated using cruise data during 1997–2014. The climatological mean of dissolved oxygen (DO) presents a “dual-core structure” below the oxycline, associated with two hypoxic centers near the river mouth and offshore of the Changjiang Bank, respectively. The DO value is highly variable from year to year, with dramatic interannual variation but an insignificant linear trend during 1997–2014. Composite analysis indicates that the interannual variation of DO and associated hypoxia events are strongly affected by the El Niño–Southern Oscillation (ENSO) cycle. In the El Niño decaying summer, large river discharge and relatively strong stratification, combined with calm climatic and hydrographic conditions, enhance DO depletion off the Changjiang Estuary. It is likely that El Niño is not a prerequisite for hypoxia occurrences. However, El Niño did enhance bottom hypoxia probability off the Changjiang Estuary during 1997–2014.